Inflammation in the brain and periphery found in animal models of depression and its behavioral relevance - Shiho Kitaoka (Elsevier, 2022)
Currently used antidepressant drugs target and facilitate the action of monoamine neurotransmission. However, approximately 30% of patients do not respond to these drugs. Therefore, there is an urgent need to develop novel therapeutic targets. Several clinical studies have reported that inflammatory cytokines and neutrophils are increased in the blood of patients with major depression. Since social and environmental stress is a risk factor for mental illnesses such as major depression, many research groups have employed chronic stress models in which mice are repeatedly exposed to stressful events. Chronic stress induces neuroinflammation originating from microglia in the medial prefrontal cortex, leading to depressive-like behavior. Moreover, chronic stress influences peripheral immune cells by activating the sympathetic nervous system and the hypothalamus-pituitary-adrenal gland axis. The infiltration of monocytes expressing interleukin (IL)-1β into the brain is involved in chronic stress-induced elevated anxiety. The penetration of IL-6 derived from monocytes into the nucleus accumbens is involved in chronic stress-induced depression-like behavior. Furthermore, cell-cell and peripheral brain interactions and their molecular basis have been discovered. These findings may pave the way for the development of biological markers and therapeutic drugs.